Hereditary myokymia and paroxysmal ataxia linked to chromosome 12 is responsive to acetazolamide. - Lubbers, W J (1995)
A sixth family with autosomal dominantly inherited myokymia and paroxysmal ataxia is described. The syndrome in this family is linked to the recently discovered locus for inherited myokymia and paroxysmal ataxia on the human chromosome 12p, and a missense mutation is shown in the KCNA1 gene. The attacks of ataxia in this family compare well with those of previously described families and similarly are precipitated by kinesigenic stimuli, exertion, and startle. Responsiveness of these attacks to low dose acetazolamide is confirmed, but some loss of efficacy occurs with prolonged treatment, and side effects are notable. Although not all affected family members showed myokymia on clinical examination, electromyography invariably showed myokymic discharges, in one patient only after a short provocation with regional ischaemia. One affected family member also had attacks of paroxysmal kinesigenic choreoathetosis, responsive to carbamazepine.